What can district migration rates tell us about London's functional urban area? - David Gray (Journal of Risk and Financial Management, 2023)
In the early 1990s, Anthony Fielding coined the term 'escalator region' to describe how London and the South East attracted those with greater human capital by offering them superior career prospects and enhanced returns in the housing markets. When delineating a housing or labour market area, it is not uncommon to require high levels of migration and commuting within the market area relative to those that cross the area's boundaries. Net migration flows to and from this escalator region change depending on the age range one examines, making migration across boundaries relatively high. It is proposed that focusing on age ranges that reflect younger adults would capture the extent of the market. In particular, the birth of a first child is likely to trigger migration, but that movement is constrained to be within the boundary of the market area. The decision to buy a dwelling would be made around the time of this event. This paper delineates market areas using spatial autocorrelation. This has the advantage of using a statistical criterion rather than a containment value. Broadly similar areas in the Greater South East are revealed using relative housing affordability measures, the movement of infants and the migration of 20- to 24-year-olds. It is argued that the time-varying patterns of migration of 30- to 39-year-olds is reflective of a change in housing affordability, forcing more households to migrate with children whilst renting.
Keywords: R12; R23; R31; 650; escalator region; house price-earnings ratios; internal migration; local authority districts; local indicators of spatial association